PENGARUH UKURAN BUTIR AGREGAT KASAR TERHADAP KAPASITAS KUAT TEKAN DAN NILAI SLUMP BETON POROUS - Samsul, Samsul; Mustakim, Mustakim; Kasmaida, Kasmaida (Jurnal Karajata Engineering, 2023)
Porous concrete is an innovation and development solution for parking areas, yards and pedestrian areas, as a way to avoid standing water or even flooding. The purpose of this study was to determine the proportion of the optimum coarse aggregate mixture for porous concrete in terms of compressive strength and slump value. The research method used was experimental research conducted at the Laboratory of Structures and Materials, Muhammadiyah Parepare University. The results of this study can indicate that the optimum mixture proportions were obtained at aggregate variations of 0.5-1 cm. The compressive strength with an aggregate size of 0.5-1 cm is 6.13 MPa, an aggregate size of 1-2 cm is 5.47 MPa, while an aggregate size of 2-3 cm is 5.00 MPa. The slump value with an aggregate size of 0.5-1 cm is 196 mm, an aggregate size of 1-2 cm is 192 mm, while an aggregate size of 2-3 cm is 178 mm.